BUDAYA 5 S ( SENYUM, SAPA, SALAM, SOPAN, SANTUN) DALAM PEMBENTUKAN KARAKTER SISWA/SISWI DI SD MUHAMMADIYAH SAPEN YOGYAKARTA - Annisa Annisa Annisa (Jurnal Teknologi Pendidikan Madrasah, 2019)
The moral crisis in the generation of the nation must be addressed through education in schools to foster the character and values of the indonesia nation. This study aims to find out how the implementation and influence of 5S (Smile, greetings,courtesy) in character formation of studens in SD Muhammadiyah Sapen Yogyakarta. The type of research used is descriptive with data collection techniques, namely: data collection observation, interviews and documentasi. Results of applying research 5S (Smile, greetings,courtesy) done at various points, including: Shool grounds, school entrances and affective posts, namely the front room of the UKS, the computer lab, and the classroom door, the implementation of this affective post is based on a predetermined. Cultural influence 5S (Smile, greetings,courtesy) have a positive impact such as: respecting the older, greeting when meeting teachers and friends, and establishing good social interactions. While outside the school environment, it can be seen through inerviews with parents that the culture of 5S (Smile, greetings,courtesy) has many influences such as: daring to start greetings to those who are older, respecting the older and greeting when entering and leaving the house.